Comparative efficacy of two paclitaxel-coated balloons with different excipient coatings in patients with coronary in-stent restenosis: A pooled analysis of the Intracoronary Stenting and Angiographic Results: Optimizing Treatment of Drug Eluting Stent In-Stent Restenosis 3 and 4 (ISAR-DESIRE 3 and ISAR-DESIRE 4) trials. (1st February 2018) - Colleran, Roisin; Joner, Michael; Kufner, Sebastian; Altevogt, Felix; Neumann, Franz-Josef; Abdel-Wahab, Mohamed; Bohner, Janika; Valina, Christian; Richardt, Gert; Zrenner, Bernhard; Cassese, Salvatore; Ibrahim, Tareq; et al.
Abstract: Background: Angioplasty with paclitaxel-coated balloons (PCB) is recommended for treatment of patients with coronary in-stent restenosis (ISR) according to European clinical practice guidelines. Most clinical trials have investigated iopromide-based PCB and there is a paucity of data comparing efficacy against butyryl-tri-hexyl citrate (BTHC)-based PCB. Our aim was to compare the performance of two widely-used PCB in the treatment of coronary ISR. Methods: We analysed patients treated with BTHC- or iopromide-PCB for treatment of drug-eluting stent ISR in the setting of 2 consecutive trials with identical inclusion and exclusion criteria. The primary endpoint was diameter stenosis at 6–8 month angiographic surveillance. The secondary endpoint of interest was the composite of death, myocardial infarction (MI) or target-lesion revascularisation (TLR) at 1 year. Multivariate analysis was performed to adjust for differences in baseline characteristics between groups. Results: In total, 264 patients were treated with BTHC-PCB ( n  = 127) or iopromide-PCB ( n  = 137). Baseline patient characteristics were similar for both groups. Post-procedure stenosis was slightly larger with BTHC-PCB (22.3 [SD 8.2]% vs. 18.4 [SD 9.9]%, P  = 0.001). At 6–8 month angiography, diameter stenosis was 40.4 [SD 21.9]% vs. 37.4 [SD 21.4]% in the BTHC-PCB and iopromide-PCB groups, respectively ( P  = 0.16, Padjusted  = 0.32). At 1 year, death, MI or TLR occurred in 29 (23.2%) vs. 32 (23.4%) patients in the BTHC-PCB and iopromide-PCB groups, respectively (HR 1.03 [95% CI 0.62–1.70], P  = 0.91, Padjusted  = 0.96). Conclusions: In patients undergoing intervention for ISR, angioplasty with BTHC-PCB showed similar angiographic and clinical results at 1 year compared with iopromide-PCB.